2020
DOI: 10.5306/wjco.v11.i6.389
|View full text |Cite
|
Sign up to set email alerts
|

National Comprehensive Cancer Network guidelines compliance of a sarcoma service: A retrospective review

Abstract: BACKGROUND Clinical workup and treatment guidelines have been published by the National Comprehensive Cancer Network (NCCN) to ensure patients are treated uniformly and appropriately. This study sought to retrospectively review patients with a new diagnosis of sarcoma who were treated in a National Cancer Institute (NCI) designated center and determine compliance rates with guidelines for sarcoma. AIM To evaluate our compliance of NCCN sarcoma guidelines at a major NCI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…A retrospective study by Blank et al carried out at a US cancer centre monitored the performance of national guidelines and showed that in 97% and 94% of cases, the imaging and pathological diagnosis were revised by the multidisciplinary tumour board, respectively. In addition, a treatment plan was discussed for each patient in an interdisciplinary tumour board [33]. Hollunder et al described that 59.1% of the recommendations of the multidisciplinary tumour board were carried out entirely and 14.4% partially in a retrospective analysis of sarcomas and musculoskeletal tumours at a German Cancer Centre.…”
Section: Access and Utilization Of An Interdisciplinary Tumour Boardmentioning
confidence: 99%
“…A retrospective study by Blank et al carried out at a US cancer centre monitored the performance of national guidelines and showed that in 97% and 94% of cases, the imaging and pathological diagnosis were revised by the multidisciplinary tumour board, respectively. In addition, a treatment plan was discussed for each patient in an interdisciplinary tumour board [33]. Hollunder et al described that 59.1% of the recommendations of the multidisciplinary tumour board were carried out entirely and 14.4% partially in a retrospective analysis of sarcomas and musculoskeletal tumours at a German Cancer Centre.…”
Section: Access and Utilization Of An Interdisciplinary Tumour Boardmentioning
confidence: 99%
“…Multidisciplinary management is best for sarcoma therapy (7)(8)(9)(10)(11)(12). Surgical resection with or without radiotherapy and chemotherapy is the standard therapy for localized sarcoma (10,13).…”
Section: Introductionmentioning
confidence: 99%
“…Surgical resection with or without radiotherapy and chemotherapy is the standard therapy for localized sarcoma (10,13). Systemic therapy has a prominent role in the multidisciplinary management of locally inoperable or metastatic sarcomas (7,14). Cytotoxic chemotherapy has been the mainstay therapy for treating advanced-stage disease, with overall response rates of approximately 25% in the first-line setting.…”
Section: Introductionmentioning
confidence: 99%